Thrombomodulin Regulation of Mitogen-Activated Protein Kinases - Giri, Hemant (Int J Mol Sci, 2019)
The multifaceted role of mitogen-activated protein kinases (MAPKs) in modulating signal transduction pathways in inflammatory conditions such as infection, cardiovascular disease, and cancer has been well established. Recently, coagulation factors have also emerged as key players in regulating intracellular signaling pathways during inflammation. Among coagulation factors, thrombomodulin, as a high affinity receptor for thrombin on vascular endothelial cells, has been discovered to be a potent anti-inflammatory and anti-tumorigenic signaling molecule. The protective signaling function of thrombomodulin is separate from its well-recognized role in the clotting cascade, which is to function as an anti-coagulant receptor in order to switch the specificity of thrombin from a procoagulant to an anti-coagulant protease. The underlying protective signaling mechanism of thrombomodulin remains largely unknown, though a few published reports link the receptor to the regulation of MAPKs under different (patho)physiological conditions. The goal of this review is to summarize what is known about the regulatory relationship between thrombomodulin and MAPKs.